A rising man - Mukherjee, Abir (Mukherjee, Abir. Sam Wyndham, 2017)
In the days of the British Raj in 1919, Captain Sam Wyndham, a former Scotland Yard detective newly arrived in Calcutta, is confronted with the murder of a British official who was found with a note in his mouth warning the British to leave India.